105-3t-32+8t-20=-72+6t-4

Simple and best practice solution for 105-3t-32+8t-20=-72+6t-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 105-3t-32+8t-20=-72+6t-4 equation:


Simplifying
105 + -3t + -32 + 8t + -20 = -72 + 6t + -4

Reorder the terms:
105 + -32 + -20 + -3t + 8t = -72 + 6t + -4

Combine like terms: 105 + -32 = 73
73 + -20 + -3t + 8t = -72 + 6t + -4

Combine like terms: 73 + -20 = 53
53 + -3t + 8t = -72 + 6t + -4

Combine like terms: -3t + 8t = 5t
53 + 5t = -72 + 6t + -4

Reorder the terms:
53 + 5t = -72 + -4 + 6t

Combine like terms: -72 + -4 = -76
53 + 5t = -76 + 6t

Solving
53 + 5t = -76 + 6t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-6t' to each side of the equation.
53 + 5t + -6t = -76 + 6t + -6t

Combine like terms: 5t + -6t = -1t
53 + -1t = -76 + 6t + -6t

Combine like terms: 6t + -6t = 0
53 + -1t = -76 + 0
53 + -1t = -76

Add '-53' to each side of the equation.
53 + -53 + -1t = -76 + -53

Combine like terms: 53 + -53 = 0
0 + -1t = -76 + -53
-1t = -76 + -53

Combine like terms: -76 + -53 = -129
-1t = -129

Divide each side by '-1'.
t = 129

Simplifying
t = 129

See similar equations:

| 2x+3x+3= | | -5=-3[x+11]-17 | | 7(5x-18)=259 | | 3(2x-9)=4(x+1) | | y=20+.9x | | 3(4.32x)+3.41y=65.48 | | 5/13=9/x | | 10(6x+2)=560 | | 3(4.32x)+3.41x=65.48 | | 1/13y=65 | | x=20+.9y | | y(y-4)=0 | | 6(x-9)=234 | | 90+51=180 | | c+51=10 | | 3x^4-192x= | | x/10-6=-3 | | 90+51+x=180 | | 4*(x+2)=-14 | | 6(5x+14)=384 | | √21/9 | | 20x^6+54x^5+10x^4= | | 9x+8=10x-13 | | Px+8=10x-13 | | ((-2)/(-5x-2))0 | | =ln(4x^2) | | 132=x+(3x-24) | | 2x=83 | | p(x)=3-5x^2+x | | 360=x+(3x-24)+132 | | tan(x+30)=2tan(x) | | 2x-5/4+x=2x+5/2+8 |

Equations solver categories